The Implementation of CSR to Enhance the Quality of Islamic Education - Andriani, Lusi; Irawan, Irawan; Sapdi, Rohmat Mulyana (STIT Ahlussunnah Bukittinggi, 2025)
This study explores the implementation of Corporate Social Responsibility (CSR) to improve the quality of Islamic education at Elementary School in Indonesia. Using a qualitative case study approach, this research examines the contribution of CSR in enhancing physical facilities and the spiritual development of students. Data was collected through interviews with the school principal, teachers, CSR program managers, and observations of the facilities. The results indicate that CSR has made a significant contribution to improving classrooms, worship spaces, and libraries, which enhances student engagement in Islamic learning and their spirituality. This study emphasizes the importance of collaboration between schools, CSR stakeholders, and the community to achieve sustainable educational improvements and create a fair learning environment in line with the broader goals of Islamic education.